Konsep Kepemimpinan Pendidikan Islam Berbasis Nilai Profetik: Kajian Literatur Filosofis dalam Perspektif Manajemen Pendidikan Islam - Uchik Rini Qomaria; Muhammad Husni (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Islamic educational leadership faces the challenge of integrating managerial professionalism with the spiritual and moral values that form the foundation of Islamic education. This study aims to analyze the concept of prophetic value-based Islamic educational leadership from a philosophical perspective and to formulate a conceptual model for the development of Islamic Education Management. Employing a library research method with a philosophical-conceptual analysis, the study examines scholarly literature on Islamic leadership, prophetic leadership, and Islamic educational management. The findings indicate that prophetic Islamic educational leadership is constructed through four main components: the philosophical foundation of tawhid and humans as khalifah; transformational orientations of humanization, liberation, and transcendence; leadership characteristics reflected in shiddiq, amanah, tabligh, and fathanah; and their implementation in educational management practices. The proposed conceptual model demonstrates that Islamic educational leadership extends beyond organizational effectiveness toward developing individuals with strong character and fostering civilized educational institutions. This study contributes to strengthening an Islamic educational leadership paradigm that integrates spiritual, moral, and managerial dimensions.